Factors Affecting Exclusive Breastfeeding in the Working Area of the Sawah Lebar Health Center, Bengkulu City - Welly Ayunda Dwi Pratiwi; Epti Yorita; Desi Widiyanti; Rina Rina; Rialike Burhan (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Breast milk is the best food for babies because it can build antibodies from an early age. Exclusively breastfeeding babies with additional food from birth to 6 months of age can prevent infectious diseases such as otiris media, diarrhea and acute respiratory infections. In Indonesia, the achievement of exclusive breastfeeding is still low due to various factors related to socio-demographics. Low access to relevant information about exclusive breastfeeding is also the cause of mothers' low knowledge about the benefits of exclusively breastfeeding their babies. Apart from that, adequate support from family and health workers also influences exclusive breastfeeding. This research aims to determine the relationship between socio-economics, family support and support from health workers on exclusive breastfeeding for babies 0-6 months in the Sawah Lebar Community Health Center area, Bengkulu City. Cross sectional research design with a sample of 98 babies aged 6-12 months selected using proportional random sampling technique. Data were analyzed univariately using a frequency distribution table, bivariately using chi square and multi variately using logistic regression. The results of the study found that there was a relationship between economic status and exclusive breastfeeding, p=0.00, there was a relationship between family support and exclusive breastfeeding, p=0.00, and there was a relationship between support from health workers and exclusive breastfeeding, p=0.00. Multivariate test results found that economic status was the most dominant factor influencing exclusive breastfeeding with a value of p=0.00. It is recommended for health workers to provide exclusive breastfeeding education in structured groups, the intervention given must take into account working mothers from middle to upper economic groups and involve family members.Keywords: Exclusive breastfeeding, economy, family, officers